2001
DOI: 10.1002/1529-0131(200103)44:3<585::aid-anr107>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase and proinflammatory cytokine production by chondrocytes of human osteoarthritic cartilage: Associations with degenerative changes

Abstract: Objective To examine by immunohistochemistry the relative distributions of 6 matrix metalloproteinases (MMPs 1, 2, 3, 8, 9, and 13) and the 2 proinflammatory cytokines interleukin‐1β (IL‐1β) and tumor necrosis factor α (TNFα) in osteoarthritic (OA) cartilage compared with normal, age‐matched articular cartilage. Methods Articular cartilage samples were obtained from the tibial plateau of OA knees removed at arthroplasty and from normal, nonarthritic, knees obtained at autopsy. Specimens were promptly fixed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
293
1
9

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 656 publications
(317 citation statements)
references
References 29 publications
14
293
1
9
Order By: Relevance
“…In contrast to RA, OA synovium and synovial fluid contain markedly lower levels of MMPs, and expression is restricted to active OA cartilage lesions, where destruction of type II collagen (CII) and proteoglycan occurs; these lesions contain MMPs 1,3,8,9,and 13. Surprisingly, the neutrophil collagenase (MMP-8) is found in arthritic lesions in the absence of neutrophils, demonstrating that chondrocytes can produce this enzyme (14,16). Comparing the 3 collagenases that are present, it is likely that MMP-13 plays a pivotal role in cartilage degradation because it is expressed by the chondrocytes and because it has the ability to hydrolyze CII more efficiently than the other collagenases (13).…”
Section: Mmps In Arthritis: Guilt By Association?mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to RA, OA synovium and synovial fluid contain markedly lower levels of MMPs, and expression is restricted to active OA cartilage lesions, where destruction of type II collagen (CII) and proteoglycan occurs; these lesions contain MMPs 1,3,8,9,and 13. Surprisingly, the neutrophil collagenase (MMP-8) is found in arthritic lesions in the absence of neutrophils, demonstrating that chondrocytes can produce this enzyme (14,16). Comparing the 3 collagenases that are present, it is likely that MMP-13 plays a pivotal role in cartilage degradation because it is expressed by the chondrocytes and because it has the ability to hydrolyze CII more efficiently than the other collagenases (13).…”
Section: Mmps In Arthritis: Guilt By Association?mentioning
confidence: 99%
“…MMPs can be inhibited at the level of gene expression, thereby reducing the amount of enzyme produced. Since multiple steps contribute to the regulation of MMP synthesis, there are numerous tar- 16 MENGSHOL ET AL gets for arthritis therapies (Figure 2), thus it is important to emphasize that therapies directed at only 1 target may be only partially effective. Inhibitors of MMP gene expression are already used in the clinic; for example, corticosteroids are commonly used in the treatment of arthritis.…”
Section: Therapeutic Inhibition Of Mmp Gene Expressionmentioning
confidence: 99%
“…Recently, a role for proinflammatory cytokines in the pathogenesis of OA was proposed based on the data from studies using human OA cartilage and various animal models [13,14]. Furthermore, direct evidence of cytokine production associated with degenerative changes in OA cartilage has been reported in a recent study [4], in which IL-1b and TNF-a were shown to co-localize with matrix metalloproteinases in the superficial zones of articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have demonstrated that one or all of these MAP kinases are involved in regulation of IL-1b and MMP gene expression [1,46]. Interestingly, a recent report indicates that human chondrocytes produce and release MMP-1 and MMP-3 when they are stimulated with IL-1 or TNF-a, but MMP-13 is produced only by cells treated with IL-1 [4]. In addition, divergent effects of IL-1b and TNF-a on chondrocyte gene expression have also been observed in rabbit and porcine articular chondrocytes [22,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…res. 54, Supplement 1 (2005) S74-S75 1023-3830/05/01S74-02 DOI 10.1007/s00011-004-0434-6 OA cartilage specimens from knee joints of 8 patients (5 female, 3 male; age 66 ± 7 years) of clinical grades 1-3 (2 grade 1; 3 grade 2; 3 grade 3) [5] were fixed within 1 h of surgical excision, in Carnoy's (for H 1 R detection) or 4% buffered formalin (for H 2 R detection) and processed to paraffin wax. For comparison, cartilage tissues from normal joints (post-mortem) were similarly processed.…”
Section: Methodsmentioning
confidence: 99%